Objective evaluation of blood flow in the small-intestinal villous: quantification of findings from dynamic endoscopy with concomitant narrow-band imaging - Takeyama, Tomoaki; Hirooka, Yoshiki; Kawashima, Hiroki; Ohno, Eizaburo; Ishikawa, Takuya; Yamamura, Takeshi; Furukawa, Kazuhiro; Funasaka, Kohei; Nakamura, Masanao; Miyahara, Ryoji; ishigami, Masatoshi; Goto, Hidemi (Endoscopy International Open, 2018)
Background and aims We have previously shown that the increase in blood flow volume in jejunum villi after spraying of 10 % dextrose solution correlates with pancreatic exocrine function (PEF). The aim of this study was to establish an objective method to evaluate the amount of jejunum villous blood flow using a novel image analysis system.Patients and methods The subjects were 26 patients who underwent upper gastrointestinal endoscopy with a newly developed small intestine endoscope (SIF-Y0007, Olympus, Tokyo, Japan). By defining the ratio of capillary occupancy in each villus at levels from 1 to 5, villous blood flow was evaluated subjectively on the villous blood flow scale (VBFS). Objective evaluation was performed based on luminance analysis. The morphological opening process was used to make images with leveled brightness. A histogram was prepared from the luminance information and the standard deviation was determined and defined as SDOV (Standard Deviation calculated from a histogram made by luminance analysis Of Villi). PEF was evaluated by measuring the BT-PABA (N-benzoyl-L-tyrosyl-p-aminobenzoic acid) excretion rate.Results There was a significant positive correlation between VBFS and SDOV (P < 0.0001, ρ = 0.5882). SDOV was also positively correlated with PEF (P = 0.0004, ρ = 0.6421).Conclusions SDOV is a new objective index for evaluation of blood flow volume in jejunum villi. SDOV may be useful in clinical practice to estimate PEF and for clarification of the mechanisms underlying the functional correlation between the pancreas and small intestine.